Technetium-99m methylene diphosphonate single-photon emission computed tomography/computed tomography of the foot and ankle - Upadhyay, Bhavin; Mo, Jonathan; Beadsmoore, Clare; Marshall, Tom; Toms, Andoni; Buscombe, John (World Journal of Nuclear Medicine, 2017)
The complex anatomy and function of the foot and ankle can make it difficult to determine the cause of symptoms in patients with foot and ankle pathology. Following initial clinical and radiographic assessment, additional imaging with magnetic resonance imaging may be required, which is often seen as the modality of choice. Although sensitive to pathological changes in bone metabolism and vascularity, technetium-99m (Tc-99m) bone scintigraphy often lacks the specificity and resolution required to evaluate the structures of the foot and ankle. Tc-99m methylene diphosphonate single-photon emission computed tomography/computed tomography (SPECT/CT) combines this sensitivity with the superior anatomical detail of CT, enabling better localization of pathological uptake and evaluation of associated structural changes. As a result, SPECT/CT has been growing in popularity for the assessment of patients with foot and ankle pathology where it can provide additional information that may change the initial diagnosis and subsequent management plan. Studies have reported modification of the surgical approach and site of intra-articular local anesthetic injections following SPECT/CT with good results. Interpretation of SPECT/CT studies requires an understanding of the pathological changes that result in increased tracer accumulation in addition to the CT changes that may be seen. This review aims to highlight the advantages of SPECT/CT, potential applications and explain the imaging appearances of common pathologies that may be observed.
Keywords: Ankle; foot; single-photon emission computed tomography/computed tomography